تأثير استخدام منهج تعليمي بملعب مصغر ووسائل مساعدة في تعلم مهارتي الارسال والتمرير من الاسفل بالكرة الطائرة - حسن, محمد توفيق (Sulaimani Journal for Humanities, 2018)
Summary As a starting point, learning basic skills in volleyball using traditional exercises are restricted and specific to the teachers of physical education, which lead to a sense of boring for learner in lesson practicing , so public workers in the field of sports seek to build a new base for the individual to teach the basic skills of the game through the provision of istructional aids to facilitate the learning process and make it more effective in time investment and effort, as far as, giving exciting , suspense and creating new ideas to the learner as well as free practicing of the performance. The researcher intends to study the impact of these instructional aids on a sample which are selected form Al-Izdehar secondary school for girls in Baqubah district. The researcher used the experimental design (experimental and control groups) with pre and post tests by applying instructional aids to achieve the goals of research. Differents statistical methods are used to extract results and to find out the significant differences between pre and post tests . The results show the impact of instructional aids in favor of the post test in learning transmitter receiver skill in volleyball using instructional aids .